Ex-utero intrapartum treatment in the Indian scenario: Anesthetic challenges and positioning - Prabha Udayakumar; Pavai Arunachalam; Vinodhadevi Vijayakumar; Gunavathi Kandappan (Wolters Kluwer Medknow Publications, 2014)
Ex-utero intrapartum treatment (EXIT) is performed for fetuses diagnosed with large neck masses. A case report of a fetus diagnosed with a large cystic hygroma and cord around the neck who was delivered by EXIT is presented. The airway challenges and optimal positioning is discussed.